Legal Protection For Consumers Against The Exoneration Clause On The Goods Stated If The Goods Are Broken Or Damaged Is The Same As Buying In The Review Of Law Number 8 Of 1999 On Consumer Protection - Simarmata, Judika; Wijaya, Andika; Sanggalang, Rizki Setyobowo (Journal of Law, Politic and Humanities, 2025)
An exoneration clause is a part of a contract that contains a provision that transfers responsibility from a creditor or business actor to another party. the basis for the creation of this clause is the principle of freedom of contract, which gives the parties the right to determine the content of their agreement. legal protection for consumers is very important to create a fair and balanced relationship between consumers and businesses. in indonesia, Law No. 8 of 1999 on consumer protection has been widely recognized, both in practice and in theory. this study aims to examine the legal responsibility in protecting consumers from exoneration clauses that are considered harmful and override the responsibility of business actors and the role of consumer protection agencies in enforcing consumer rights against adverse exoneration clauses. this research uses normative juridical research methods, namely research that focuses on the analysis of legal norms that apply in a legal system. this method aims to explore and evaluate legislation, legal doctrine, and existing legal principles, without involving empirical data or field observations. this study concluded that the legal responsibility to consumers is derived from the consumer protection law1 no. 8 of 1999 provides a legal framework to protect consumer rights, including prohibiting the inclusion of adverse standard clauses and forms the role of consumer protection institutions is that they supervise, provide education, and help resolve disputes, as well as encourage changes to stricter regulations.